ALTERNATIF DESAIN SALURAN PEMBAWA PADA PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DI DESA BENDOSARI KABUPATEN MALANG - Harsanti, Moch. Khamim, Winda (Prokons: Jurnal Teknik Sipil, 2016)
Electric energy is important requirement for human activities, and much of this energy is still filled by non renewable energy. In certain time, this source will deplet. To solve this problem, subtitution energy must be founded. Water is one of the renewable energy which can be substitution to produce electrical energy. Water from the water springs will be flowed to power house, before changing to electrical energy, through water way. The aim of this study is to determine alternative of water way. Discharge that is used on this study based on measurement. From those measurements, design discharge is determined by 0,3 m3/dt. The water way will be designed as open channel using eight alternatives, and will be chosen best alternative for recommendation. Keywords: design discharge, open channel, water way